Effect of the herbicide 2,4-dichlorophenoxyacetic acid on uropathogenic Escherichia coli virulence factors - Balague, Claudia Elisabeht (2002)
The effects of the herbicide 2,4-dichlorophenoxyacetic acid (2,4-D) - widely used in the world and mainly excreted by the renal route in exposed humans - were studied on the virulence and surface characteristics of an uropathogenic Escherichia coli strain. When the urine was supplemented with 2,4-D in vitro, the compound significantly reduced the bacterial fimbriation assayed by hemagglutination and surface protein quantification. Protein values decreased from 0.24 mg/g dw to 0.05 or 0.12 mg/g dw by 1 or 0.1 mM 2,4-D treatment, respectively. The effects in vivo were studied in groups of mice challenged intra-urethra with E. coli and exposed by the oral route with three different 2,4-D doses (2.6, 25 or 70 mg/kg bw) during 22 days. Depending on the dose used, the herbicide significantly decreased or removed bacterial cells in mice bladder and kidneys; except in the group treated with the highest dose from the 9th day of treatment. The histological studies showed mononuclear cell infiltration at low doses, and toxic damage in the renal parenchyma at prolonged exposure with higher doses, up to tisular necrosis in the 70 mg/kg bw group after 9 days of treatment. Our investigations performed in an experimental model suggest that short time 2,4-D exposure at low doses could act in prevention of UTI stimulating leukocytic migration and decreasing bacterial fimbriation. On the contrary, high doses and long-term exposure enhanced renal damage resulting in infection recurrence.